Correlation of offspring thyroid function and maternal iodine status in iodine deficient-coastal area - Ekawanti, Ardiana; As’ad, Suryani; Natsir, Rosdiana; Umar, Husaini; Irawati, Deasy; Kadriyan, Hamsu; Zubaidi, Fitriannisa Faradina; Ayunda, Rahmah Dara (Intelektual Pustaka Media Utama, 2024)
Thyroid hormone is vital for children's growth and metabolism, relying on sufficient iodine levels for synthesis. Maternal intake determines iodine supply to fetuses and children under two years old. This study aimed to correlate offspring thyroid function with maternal iodine status in coastal areas. A cohort study was conducted, involving pregnant coastal residents. Maternal urinary iodine levels were measured via the ammonium persulfate method, while offspring thyroid stimulating hormones (TSHs) and free thyroxine hormone (fT4) levels were assessed using electro-chemiluminescence immunoassay (ECLIA). Iodine intake was determined through a semiquantitative food frequency questionnaire (FFQ). The correlation between offspring thyroid function and maternal iodine status was analyzed using Pearson’s correlation test. Differences in TSHs and fT4 levels among iodine status groups were examined using the One way-ANOVA test. Maternal iodine status was insufficient with a median urinary iodine of 125 μg/L, resulting in a 60.8% prevalence of iodine insufficiency. Iodine intake (62.20±43.45 μg/day) fell short of recommended levels (RDA). Offspring TSH was 2.29±1.07 μIU/mL, fT4 was 1.26±0.14 ng/dL. TSH and fT4 concentrations showed no significant inter-group differences (p=0.852, p=0.075). Offspring thyroid function did not correlate with maternal iodine status (TSHs: p=0.314; fT4: p=0.258). Offspring thyroid function did not correlate to maternal iodine status in a population of iodine-insufficient and mercury-contaminated coastal areas.